PENDIDIKAN KESADARAN KEARIFAL LOKAL CUCI NEGERI DAN IMPLEMENTASINYA DALAM PEMBELAJARAN IPS MELALUI PENDEKATAN ECOPEDAGOGY PADA SMP DI KOTA AMBON - Bety Diana Serly Hetharion, - (2019)
The phenomenon of environmental damage that has become a global issue, has threatened all dimensions of human life. The local wisdom of cuci negerior village cleansing can be used to develop students' awareness to care for the environment and build a better life. This study aims to explore the values of local wisdom,cuci negeri, and its implementation in awareness education in social studies learning through the ecopedagogy approach. This study uses qualitative approach with ethnographic methods and classroom action research (CAR). Ethnographic research took place in villages in Ambon city at four schools, namely State Junior High School 2, State Junior High School 3, State Junior High School 10 and Middle School 15 Ambon. Ethnographic research produces the value of local wisdom, namely the value of caring for the environment, religious values, values of responsibility, social values and democratic values. The values of local wisdom are implemented through Eliot's model classroom action research (CAR). The results of class action research show, 1) The values of village cleansing local wisdom have been successfully integrated with IPS or social studies material in the 2013 curriculum as material for awareness education through the ecopedagogy approach, 2) The integration of learning has shaped the awareness of students about the importance of applying cuci negeri values in everyday life. 3) The ecopedagogy approach was successfully developed through indoor and outdoor environmental learning using social inquiry methods, demonstrations, role play, and field trips. The ecopedagogy approach can develop moral knowledge, moral feelings and moral actions of students in four schools used as subjects of this research. This is reflected in the increase in learning outcomes, social attitudes and moral actions of students after the implementation of environmental, religious, responsibility, social and democratic values in social studies learning. Education on awareness of local wisdom, cuci negeri, in social studies learning through the ecopedagogy approach, can be the key to developing good characters in junior high school students in Ambon City. Keywords: Awareness Education, Local Wisdom of Cuci Negeri, Social Studies Learning and Ecopedagogy Approach.